Inequality and Regional Development within the European Union - Roberto Ezcurra; Carlos Gil; Pedro Pascual; Manuel Rapún (European Regional Science Association (ERSA), 2003)
The aim of this paper, which forms part of a wider research project, is to analyse changes in regional disparity in the European Union between 1977 and 1999 by calculating the level of internal and external inequality in various groupings of regions. Our calculations are based on the Theil (0) and Theil (1) indices commonly used in the literature dealing with inequality. The regions are grouped by countries, economic development level and sectoral specialisation. After observing the evolution of internal and external disparity in the different geographical groupings, we assess the impact of politics and economic development on the various outcomes.
Keywords: 330